CARING FOR A NEW NORMAL MOTHER I CARING FOR A NEW NORMAL MOTHER IN THE NEW NORMAL TIME BREAST CARE COUNCEMENT TO PUBLIC MOTHER IN THE ACADEMY OF MIDWIFERY IN AL BAETI BULUKUMBA - S.ST., M.KES, JUSNI; Badasari, Suci; Irnawati, Irnawati (Poltekkes Kemenkes Riau, 2023)
Postpartum or the puerperium starts from 1 hour after the birth of the placenta to 6 weeks (42 days) after that. Parents, especially mothers, need to have knowledge and readiness to conceive, give birth and breastfeed their children. Breast care is an important part that must be considered in preparation for later breastfeeding. Report from the Indonesian Demographic and Health Survey (IDHS, 2007) aged more than 25 years, one third of women in the world (38%) are found not to breastfeed their babies because of breast engorgement. The materials used in this community service are counseling materials, leaflets, and demonstration tools for carrying out breast care for postpartum mothers. Of the 20 mothers who have been given counseling and demonstrations, they understand how to do breast care for postpartum mothers and are able to answer questions properly and correctly and all postpartum mothers who from the start do not understand and understand how to do breast care for postpartum mothers and its uses. Counseling by health personnel and forming a class for postpartum mothers is very much needed by the community, so it is hoped that knowledge on how to do breast crare for postpartum mothers can increase so that they can do it at home with husbands to reduce complaints on the breasts of postpartum mothers and reduce complications Keywords: postpartum, counseling, Breasrcare, midwife